Świat emocji w powieści Sergieja Dawydowa Springfield - Trojanowska, Urszula (Slavia Orientalis, 2024)
In the article, I focus on Sergey Davydov's debut novel Springfield, published in 2023. I am primarily interested in the emotional world of the characters, but it is impossible to ignore the fact that the work itself is an extremely emotional text, influenced by its writing style (free verse later transformed into prose). It is also noteworthy that the novel was published by an independent publishing house without a fixed location, which prints books that cannot be published in Russia but that represent a cry that must reach an audience. The novel about two young gay men from the Russian provinces carries a poignant message, further amplified by the context of the ongoing war in Ukraine. The characters are filled with complex emotions, which are expressed in their creative work. Deprived of symbolic representation, the boys create works about themselves, which helps them survive in a harsh reality.